2004
DOI: 10.1212/01.wnl.0000140708.62856.72
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameter: Treatment of postherpetic neuralgia: [RETIRED]

Abstract: Abstract-A systematic review of the literature on postherpetic neuralgia was performed. The authors identified studies using the National Library of Medicine's Medline database and Cochrane Library database. The authors determined absolute reduction rate, number needed to treat (NNT), 95% CI for NNT, and number needed to harm (NNH) for successful therapies of postherpetic neuralgia. Tricyclic antidepressants, gabapentin, pregabalin, opioids, and lidocaine patch were found to be effective in reducing the pain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(63 citation statements)
references
References 55 publications
0
60
0
3
Order By: Relevance
“…Our levels of evidence are in agreement with the assessments of the Quality Standards Subcommittee of the American Academy of Neurology. 75 There is a need for randomized controlled studies on the efficacy of interventional treatments of PHN either because drugs are not always effective, as shown in our case report, or because their adverse effects limit their dose. Intrathecal alcohol should be considered only in resistant cases of PHN.…”
Section: Pharmacological Management Of Phnmentioning
confidence: 88%
See 1 more Smart Citation
“…Our levels of evidence are in agreement with the assessments of the Quality Standards Subcommittee of the American Academy of Neurology. 75 There is a need for randomized controlled studies on the efficacy of interventional treatments of PHN either because drugs are not always effective, as shown in our case report, or because their adverse effects limit their dose. Intrathecal alcohol should be considered only in resistant cases of PHN.…”
Section: Pharmacological Management Of Phnmentioning
confidence: 88%
“…RCTs support efficacy *Two studies showed the efficacy of topical capsaicin, but the magnitude of pain relief may not be clinically important. 75 RCT indicates randomized controlled trial. …”
Section: Pharmacological Management Of Phnmentioning
confidence: 99%
“…Two further systematic reviews9 , 10 of evidence on treatments for postherpetic neuralgia both included the randomised trials described above,5 , 6 and also a trial of 5% lidocaine gel applied topically 11. The authors of both reviews concluded that topical lidocaine was effective in reducing the pain of postherpetic neuralgia based on strength of evidence and low level of unwanted effects.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Opioids have been shown to be effective in the treatment of postherpetic neuralgia [5] and painful diabetic neuropathy [6]. Opioids are included in the current treatment guidelines by the American Academy of Neurology for the treatment of postherpetic neuralgia [7] and by the European Federation of Neurological Sciences for painful polyneuropathy [8] based on these studies. Despite this growing body of evidence supporting their use, clinicians hesitate to administer opioids to a patient with severe neuropathic pain unrelieved by standard treatment.…”
Section: Introductionmentioning
confidence: 99%